IMPACTS OF POLITICAL INSTABILITY ON BANK PERFORMANCE: (EVIDENCE FROM ETHIOPIAN BANKING SECTOR) - Alemu Ademe (ZILLZELL MEDIA PRIMA, 2023)
The soundness of the banking sector is very important because they play a pivotal role in economic growth. This article sought to investigate the Impacts of political instability on financial institution performance evidence from Ethiopian banks. The study employed 16 out of 26 banks due to the availability of audited panel data from the National Bank of Ethiopia (NBE) and the ministry of finance and economic development (MoFED), for the period ranging from 2013 to 2021. For the study, the panel regression model was employed. The study used two common measures of performance, proxied by either ROA or ROE as the dependent variables. Eight independent variables are also used. The descriptive and multiple linear regression analyses were done. The results documented that political violence & ethnic conflicts, and inflation have a significant negative effect on ROA and ROE, but non- performing loans have a significant and negative effect on ROA and a significant and positive effect on ROE, while deposit volume, operational efficiency, financial risk, and GDP have a positive and significant effect on ROA and ROE. The finding also reveals liquidity has a positive and insignificant effect on ROA and ROE. Political instability is a serious problem for the sustainable development of the country's banking sector. Thus, the study gives worthy acumens for the Government, regulators, and interested parties for enhancing the performance of the banking sector in Ethiopia.